Leveraging Artificial Intelligence for Transformative Religious Studies Education Curriculum in Nigeria: Teachers' Perspectives - Nwadiokwu, Christiana N (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This study aimed to explore teachers' perspectives on the integration of Artificial Intelligence (AI) in Religious Studies Education Curriculum in Nigeria, with a focus on the potential benefits and challenges of AI integration. The study employed a survey research design, collecting data from 1000 teachers in Nigeria using a self-developed questionnaire.The study's conclusions show that while teachers view AI as a useful tool to enhance Religious Studies Education teaching methods, they also voice concerns about the lack of support and training for integrating AI, the possible dangers of relying too much on technology, and epistemic limitations. The report also suggests methods for integrating AI effectively, such as creating a comprehensive strategy that strikes a balance between the advantages of AI and the need for critical thinking, human contact, and spiritual development. The study comes to the conclusion that while AI has the potential to improve Religious Studies education, educators and policymakers must carefully weigh the advantages and disadvantages of integrating AI to make sure that it helps students develop their critical thinking, spiritual literacy, and problem-solving abilities.. Based on the findings, the study recommends that educators develop a holistic approach to AI integration, teach AI literacy, and ensure data privacy and security, while policymakers provide training and support for teachers and develop guidelines for AI integration. By understanding teachers' perspectives and developing effective strategies for AI integration, educators can promote deeper learning, spiritual growth, and critical thinking in students.